ChemInform Abstract: A Deacetylation—Diazotation—Coupling Sequence: Palladium‐Catalyzed C—C Bond Formation with Acetanilides as Formal Leaving Groups. Issue 30 (4th July 2013) - Schmidt, Bernd; Berger, Rene
Abstract Acetanilides (I), (VI), and (VIII) can be deacetylated and diazotized in situ, and subsequently used in Pd‐catalyzed coupling reactions without isolation of the diazonium intermediate.